2016
DOI: 10.1093/jhps/hnw027
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of proximal deep vein thrombosis after elective hip arthroscopy: a prospective cohort study in low risk patients

Abstract: Prospectively assess the incidence of deep venous thrombosis (DVT) using Doppler Ultrasound, in patients receiving elective hip arthroscopy without pharmacologic/mechanical prophylaxis. One hundred and fifteen consecutive patients (mean 35.4 years, SD = 10.3) underwent elective hip arthroscopy. Patients with previous major risk factors for DVT were excluded. Signs/symptoms of DVT/pulmonary embolism were assessed at 2-week post-operatively. A bilateral whole leg Duplex color (Doppler) Ultrasonography was schedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Hip arthroscopy has been used to treat various disorders of the hip [ 58–61 ]. The incidence of VTE after hip arthroscopy has been reported to be between 0 and 6.94% [ 14 , 15 , 62–67 ] ( Table II ). In a recent systematic review on VTE after hip arthroscopy, Haldane et al .…”
Section: Current Evidences Regarding Prevention Of Vte After Hpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hip arthroscopy has been used to treat various disorders of the hip [ 58–61 ]. The incidence of VTE after hip arthroscopy has been reported to be between 0 and 6.94% [ 14 , 15 , 62–67 ] ( Table II ). In a recent systematic review on VTE after hip arthroscopy, Haldane et al .…”
Section: Current Evidences Regarding Prevention Of Vte After Hpsmentioning
confidence: 99%
“…Mohtadi et al . [ 62 ] conducted a prospective cohort about incidence of VTE after hip arthroscopy that had multiple superiorities comparing to former studies. They excluded patients with previous risk factors for VTE, employed ultrasound and MDCT in order to screen for VTE and found asymptomatic patients and also tried to stratify the surgical risk factors for VTE.…”
Section: Current Evidences Regarding Prevention Of Vte After Hpsmentioning
confidence: 99%
“…Fukushima et al [ 12 ] reported 6.94% incidence of DVT in a cohort of 72 patients. Mohtadi et al [ 13 ] also used Doppler ultrasound to screen patients for DVT on days 10–22 after hip arthroscopy and reported an incidence of 4.3% (4 cases). Ultrasound screening for the development VTE after orthopaedic procedures is not currently recommended in asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Mohtadi et al [ 13 ] detected one case of asymptomatic DVT by ultrasound screening of a group of low-risk patients who underwent hip arthroscopy in a prospective study. Fukushima et al [ 12 ] detected five asymptomatic cases of DVT (confirmed by ultrasound) in a group of 72 patients who underwent hip arthroscopy for FAI syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A study from our own institution found that the incidence of DVT was \ 4% following elective hip arthroscopy, which further confirms the safety of the procedure with regard to venous thromboembolic events. 66 While current guidelines are lacking for DVT prophylaxis following hip arthroscopy, early mobilization is recommended for all patients and routinely used in our institution. In addition, prophylactic administration of unfractionated heparin 5,000 IU subcutaneously should be considered for patients at increased risk for thromboembolic events, such as a personal history of hypercoagulable syndromes and venous thromboembolism.…”
Section: Deep Vein Thrombosismentioning
confidence: 99%